2014
DOI: 10.1080/02681102.2014.899961
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Factors Affecting e-Commerce Adoption among Small- and Medium-Sized Enterprises in a Developing Country: Evidence from Malaysia

Abstract: The purpose of this paper is to empirically examine determinants of e-commerce adoption among Malaysian small-and medium-sized enterprises (SMEs). This study tested eight hypotheses on determinants affecting e-commerce adoption with empirical data from several survey instruments: an online questionnaire-based survey, mailed survey and questionnaire collected in-person from a sample of 307 SMEs in Malaysia. The findings show that e-commerce adoption within Malaysian SMEs is affected by perceived relative advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
126
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(178 citation statements)
references
References 65 publications
(88 reference statements)
16
126
1
10
Order By: Relevance
“…Relative advantage is the most significant factor that affects e-commerce continuance intention. This similar to the previous studies such as Alam et al (2011) and Ahmed et al (2015) suggested when e-commerce as perceived relative advantage as being better than the idea it supersedes, and beneficial to SMEs, its adoption is more likely.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Relative advantage is the most significant factor that affects e-commerce continuance intention. This similar to the previous studies such as Alam et al (2011) and Ahmed et al (2015) suggested when e-commerce as perceived relative advantage as being better than the idea it supersedes, and beneficial to SMEs, its adoption is more likely.…”
Section: Discussionsupporting
confidence: 78%
“…TOE framework is consistent with Rogers' (2003) diffusion of innovation theory as it focuses on both internal and external characteristics of the organization, as well as technological characteristics in the study of drivers for new technology diffusion as shown by Ahmed et al (2015). TOE framework can be combined with DOI theory.…”
Section: Research Model and Hypothesis Of This Studymentioning
confidence: 81%
“…Over the past decade, various factors have been proposed and tested by researchers to determine what factors afect the adoption of e-commerce [7]. According to most current research, however, it is considered that businesses successful in adopting e-commerce are strongly dependent on the local business culture.…”
Section: Introductionmentioning
confidence: 99%
“…According to most current research, however, it is considered that businesses successful in adopting e-commerce are strongly dependent on the local business culture. While these studies atempted to investigate the factors that inluence e-commerce adoption to be carried out mainly in developed nations [7], these factors have not always been consistent across studies [8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, using internet and communication technologies for conducting business and creating a competitive edge has emerged as one of the most important development trend in last decade (Ahmad, Abu Bakar, Faziharudean, & Mohamad Zaki, 2015) [1] . International trade is taking a new form with the spread of internet and e-marketing activities (Eid, 2005[16]; Ivanauskiene, Auruskeviciene, Ramoniene, & Skudiene, 2015) [25].…”
Section: Introductionmentioning
confidence: 99%